(untitled) - Tisdale, Stacey (Hoboken, N.J., 2007)
In The True Cost of Happiness, financial journalist Stacey Tisdale and expert financial planner Paula Boyer Kennedy combine their extensive financial experience with a powerful series of interviews and real-world stories to help you make personal money management decisions that make more sense. They begin by discussing how the factors that drive our financial choices and behavior not only run deep, but also represent the way we define ourselves. From there, they reveal how this truth will determine if you can create the kind of financial harmony that not only supports the life you want, but also makes an honest statement of who you really are. The questions they pose are challenging, but essential, because if your financial choices and behavior are not aligned with your true values, you'll always feel like "something" is missing. And it is this disconnect that is at the root of most anxiety and unhappiness over money.
Keywords: Finance, Personal,Awareness,Self-actualization (Psychology),Tài chính, Cá nhân,Tự hiện thực (Tâm lý); Psychological aspects,Khía cạnh tâm lý